Flow‐based in vivo NMR spectroscopy of small aquatic organisms. (11th July 2019) - Soong, Ronald; Liaghati Mobarhan, Yalda; Tabatabaei, Maryam; Bastawrous, Monica; Biswas, Rajshree Ghosh; Simpson, Myrna; Simpson, Andre
Abstract: NMR applied to living organisms is arguably the ultimate tool for understanding environmental stress responses and can provide desperately needed information on toxic mechanisms, synergistic effects, sublethal impacts, recovery, and biotransformation of xenobiotics. To perform in vivo NMR spectroscopy, a flow cell system is required to deliver oxygen and food to the organisms while maintaining optimal line shape for NMR spectroscopy. In this tutorial, two such flow cell systems and their constructions are discussed: (a) a single pump high‐volume flow cell design is simple to build and ideal for organisms that do not require feeding (i.e., eggs) and (b) a more advanced low‐volume double pump flow cell design that permits feeding, maintains optimal water height for water suppression, improves locking and shimming, and uses only a small recirculating volume, thus reducing the amount of xenobiotic required for testing. In addition, key experimental aspects including isotopic enrichment, water suppression, and 2D experiments for both 13 C enriched and natural abundance organisms are discussed. Abstract : In vivo NMR spectroscopy provides a unique insight into living processes and responses. When combined with novel line‐narrowing approaches or multidimensional NMR, a wide range of metabolites can be identified. No other analytical technique can provide such a wealth of molecular‐level information in a noninvasive manner. As such in vivo NMR represents a key tool for the next generation of research and will likely be central to understanding sublethal toxicity, including bioaccumulation, biotransformation, synergistic effects, toxic response pathways, and recovery.